Multistage precipitation triggering 3 GPa compressive strength and superior corrosion resistance in a FeCrVNiAl alloy - Mingze Wang; Yongfeng Shen; Nan Jia; Wenying Xue; Xinli Wang (Materials Futures)
High compressive strength combined with excellent anti-corrosion property is an urgent demand for marine drilling platform. Here we achieve superior combination of mechanical property and corrosion resistance of the Fe _30 Cr _15 V _15 Ni _20 Al _20 eutectic high entropy alloy (EHEA) via solid solution and aging treatments. Hierarchical precipitation of nanosized B2 (NiAl) and L2 _1 (Fe _2 CrV) phases occurs within the BCC matrix and B2 phases, respectively. Consequently, the alloy exhibits an ultrahigh compressive strength (yield strength of 2330 MPa and ultimate strength of 3050 MPa) and remarkable compressive strain of 28%. The exceptional strain hardening is achieved by sequentially triggering a synergic strain-hardening mechanisms including the first stage of precipitation hardening and the hardening jointly contributed by Lomer–Cottrell lock, as well as the misfit dislocations induced coherent interface in the second stage. Moreover, this alloy also demonstrates excellent corrosion resistance, evidenced by a low corrosion current density (6.42 × 10 ^−6 A cm ^−2 ) and stable passive film formation. These findings establish a novel microstructural design strategy for EHEAs to achieve mechanical-corrosion balance in marine environments.